Comparison of oral health behaviour between dental and non-dental undergraduates in a university in southwestern China--exploring the future priority for oral health education - Mingming Li; Zhiwu Wu; Rui Zhang; Lei Lei; Siqi Ye; Ran Cheng; Tao Hu (BMC, 2020)
Abstract Background Based on a national survey in 2015, people's oral health behaviour (OHB) has not kept up with the pace of knowledge and attitudes in China after decades of oral health education (OHE). Thus, we need to improve OHE to strengthen people's OHB. Undergraduates are regarded as the best candidates for the improvement of OHE. The objective of this study is to determine undergraduates' oral health status and existing problems in OHB by comparing dental and non-dental students at Sichuan University. We hope to provide some suggestions for future OHE to improve people's OHB. Methods A quasi-experimental study designed with a pre-test and post-test group was conducted. A total of 217 dental students and 135 non-dental students were enrolled. They were administered an OHE course focused on OHB. A survey about oral health behaviour and knowledge was conducted before and after the course. Results According to the pre-course survey, dental students surpassed non-dental students in terms of toothbrushing frequency, method, and time, but unfortunately, flossing was overlooked by all the students. After the course, both dental and non-dental students showed strong willingness to improve their OHB. More non-dental students than dental students were willing to use toothpicks and Chinese herbal toothpaste before and after the course. Conclusions OHE focused on behaviour has a positive effect on university students. Future OHE and interventions should focus on flossing, toothbrushing methods, toothpicks, Chinese herbal toothpaste and modifications to adopt new media.